Real-Time Analysis of Temperature Changes in Composite Increments and Pulp Chamber during Photopolymerization. (18th October 2015) - Kim, Ryan Jin-Young; Lee, In-Bog; Yoo, Jin-Young; Park, Su-Jung; Kim, Sin-Young; Yi, Young-Ah; Hwang, Ji-Yun; Seo, Deog-Gyu
Abstract : Objective . The aim of this study was to evaluate the temperature change at various sites within the composite and on the pulpal side of dentin during polymerization of two composite increments. Materials and Methods . Class I cavities prepared in third molars were restored in two composite increments (n = 5 ). Temperatures were measured for 110 s using eight thermocouples: bottom center of cavity (BC), top center of 1st increment (MC), top center of 2nd increment (TC), bottom corner of cavity (BE), top corner of 1st increment (ME), top corner of 2nd increment (TE), pulpal side of dentin (PD), and center of curing light guide tip (CL). Results . Maximum temperature values (°C) measured during polymerization of 1st increment were MC (59.8); BC (52.8); ME (51.3); CL (50.7); BE (48.4); and PD (39.8). Maximum temperature values during polymerization of 2nd increment were TC 58.5; TE (52.6); MC (51.7); CL (50.0); ME (48.0); BC (46.7); BE (44.5); and PD (38.8). Conclusion . Temperature at the floor of the cavity was significantly higher during polymerization of 1st increment compared to 2nd increment. Temperature rise was higher at the center than at the corner and at the top surface than at the bottom surface of each increment.